1990
DOI: 10.1177/039219219003815001
|View full text |Cite
|
Sign up to set email alerts
|

Aphasia - the Worm's Eye View of a Philosophic Patient and the Medical Establishment

Abstract: If you were trained as a philosopher and were suddenly bereft of speech, writing and reading, how would you feel? Would you feel a sensation of death, or Nirvana, or unconscious or conscious loss of control? Would you feel scientifically objective, or full of Aristotelian wonder? Would you think you were having a supernatural experience?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…People with aphasia have reported that others' responses to it have a significant impact on how they live their life. Alexander (1990) describes how he felt confused and frustrated when his speech and language therapist did not consider his interests and life history in designing therapy tasks and how this undermined his self‐esteem. Newborn (1997), on the other hand, outlines her fear of being judged negatively by others and by being ignored by society.…”
Section: Introductionmentioning
confidence: 99%
“…People with aphasia have reported that others' responses to it have a significant impact on how they live their life. Alexander (1990) describes how he felt confused and frustrated when his speech and language therapist did not consider his interests and life history in designing therapy tasks and how this undermined his self‐esteem. Newborn (1997), on the other hand, outlines her fear of being judged negatively by others and by being ignored by society.…”
Section: Introductionmentioning
confidence: 99%